Processes of Intellectualization of Business Activities of Enterprises on the Oil and Gas Industry: Diagnostics of Employees - Кісь, С. Я.; Кісь, Г. Р. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
A complex of measures of diagnostics of staff of enterprises of oil and gas complex of Ukraine was proposed, aiming at establishing the preconditions, peculiarities, problems and prospects of intellectual activitiy of subjects of business. A diagnostic toolkit that was used can be divided into three parts: first - establishment of the lefel of readiness of managing and executive staff of oil and gas enterprises for the processes of the processes of intellectualizaation through distribution and generalization of author’s survey; second - determining the real and necessary conditions of intellectualization of activity of oil and gas enterprises based on the results of the survey; third - assassment of the level of intellectualization of managers and executives, the use of tools of production based on well-known methods of assessment that allow to identify the level of quaities characteristic for an intellectual employee. The following enterprises were chosen for the analysis: «Naftogaz of Ukraine», «Ukrtransgaz», «Ukrnafta», «Ukrgazvydobuvannya», «Ukrtransnafta». The selection of managing and executive staff was made based on the overall number of employees of the enterprises, number of structural divisions, staff that manages main and supporting business processes. Theoretical methodological approaches and results of the research of the enterprises that were gathered confirm the possibility of use of the diagnostic toolkit for the assessment of the state and prospects of the processes of intallecualization by the businesses of other industries of national economy.